Novel membranes based on cellulose for gas separation and green method for their preparing - Filistovich, Valeryia B.; Savitskaya, Tatsiana A.; Kimlenka, Irina M.; Hrynshpan, Dzmitry D.; Makarevich, Svetlana E.; Teplyakov, Vladimir V.; Syrtsova, Daria A. (Journal of the Belarusian State University. Chemistry, 2019)
A «green» method of obtaining gas separation composite membranes from cellulose solutions and its mixtures with chitosan in orthophosphoric acid is proposed for industrial use, and differs from the viscose method of producing cellophane and other known methods for producing cellulose gas separation membranes without gaseous emissions and wastewater. It is shown that new composite cellulose membranes on a viscose fabric substrate are characterized by high productivity and selectivity for O2/ N2 pairs, comparable to the values obtained for known membranes made of synthetic polymers, as well as increased mechanical strength. The developed composite membranes demonstrate an inverse selectivity for the CH4/CO2 pair, which is not typical for gas separation membranes described in the literature with cellulose-based selective layers.